Geralt of Poland: The Witcher 3 Between Epistemic Disobedience and Imperial Nostalgia - Majkowski, Tomasz Z. (Open Library of Humanities, 2018)
This article is a reading of The Witcher 3 in relation to postcolonial approaches to Polish culture. It departs from an analysis of an online debate on racial representation in the game as a possible act of epistemic disobedience, and moves on to a consideration of three narrative aspects of the game itself: its representation of political struggle, the ideological stance of the protagonist, and ethnic inspirations in worldbuilding. By referring those three issues to postcolonial analyses of Polish culture, as well as Walter D. Mignolo’s concept of decolonization through epistemic disobedience, this article aims to demonstrate paradoxical qualities of the game, which tries to simultaneously distance itself from the established, West-oriented ways of knowledge production and gain recognition as an artifact of modern Western pop culture. Moreover, it employs the tradition of Polish Romanticism to establish itself as a bridge between Slavdom and Western culture, and strengthen the colonial idea of Poland being the proper ruler over Slavs.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé